Waqf ilmi in UiTM Negeri Sembilan; creating awareness and acceptance through A-I-D-A model perspective - Ibrahim, Sıtı Sara; Musa, Aini Hayati; Baharuddin, Farrah Nadia; Ratul Maknu, Tengku Sharifeleani; Ramli, Abdul Halim (2017)
Purpose - The future success of socio-economic wellbeing significantly contributed from the nation’s education other than the economic growth. Knowledge should be the main aspect that need to be considered by a human to growth, even Islam itself is emphasized by the very first word of the first verse revealed in the Quran, “iqra” which literally means read. In fact, education is important for a sustainable development of the society other than to reduce poverty and otherreligious purposes.Responding to this issue, waqf in higher education started growing as a mechanism in developing knowledgeable intellectuals other than providing an infrastructure for educational purposes. Through this, individual can contribute to the society not only by having cash or assets, but also by contributing the knowledge and expertise to the community which is called as “waqf ilmi”. The unique features and good track of waqf in the prominent universities in the world has raised awareness for public universities in Malaysia to adopt waqf.However, the level of awareness should be instilled at an early date of the introduction of waqf ilmi as the waqf concept in Malaysia, specific in higher education is still at perceived level and less satisfactory.Hence, to foster the practice of waqf in higher learning institution, this study aims to promote the fundamental understanding by creating an awareness towards waqf ilmi within the community in Universiti Teknologi MARA (UiTM), Negeri Sembilan.A study starts with an explanation of waqf ilmi and how it can be implemented here.Then, a structured questionnaire was distributed to whom were selected randomly within 3 campuses of UiTMCNS to share their understanding and awareness on waqf ilmu using A-I-D-A model as a benchmark of measurement. The result of this study can be used as a starting point by various parties to promote waqf ilmi as a norm of educational development of the society.Methodology - Waqf has been executed to benefit in many aspects not only limited to religious purposes but also education, healthcare, national security, commercial and business activities, transportation facilities, shelter and food for the needy and poor. The awareness and correct understanding of waqf should be possessed by -R Hussin, RA Rashid (2017).